Ondas bicromáticas e bidirecionais: aplicação da transformada de Hilbert-Huang às velocidades orbitais - Souza e Silva, Mario Grüne de (2019)
Bimodal spectra are quite a common feature in many places around the world, either on the open coast or within estuarine environments. They may often be thought of as group of collinear waves with two primary frequencies. However, it is important to consider that these spectra may be the result of the superposition of two independent wave systems with different directions, containing multiple wave-wave interaction components. The aim of this study is to investigate Bichromatic-Bidirectional (Bi-Bi) waves to characterize the wave-wave nonlinear interactions, using adaptive techniques rather than traditional spectral techniques. A physical model test in a 3D wave basin was conducted and measurements were made with two arrays of ultrasonic sensors of free surface and one array of ADVs. The Hilbert-Huang Transform (HHT), aided by the Multivariate Empirical Mode Decomposition (MEMD), was applied to the orbital velocity data and the main characteristics of the subtractive interaction wave (velocity amplitude, period and direction) were extracted with a good precision. Equations for the radiation stresses resulting from a Bi-Bi system were developed. The results show that the oscillation generated by the subtractive wave-wave interference, commonly associated to the infragravity wave, is capable of generating hydrodynamic currents even outside the surf zone and in a flat bathymetry, and suggest the importance of considering the nonlinear terms in numerical models when two or more systems approach the shore.